Notes on Theories of Conservation – Colonialism, Obsolescence, Misreading - Pedro Augusto Vieira Santos (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Even though there have been constant discussions about the theoretic and ethical questions of conservation, the scientific production in recent years demonstrates the difficulty of arriving at consensual opinions and formulations – which is not a problem. The problem is the shakiness of some of these opinions or formulations, which can be explained by some ghosts that still haunt scientific production generally: Colonialism, Obsolescence and Misreading. The present article sheds light on these problems and points out possible paths, based on authors in the field of conservation, on the punctual analysis of their productions, and on the way their ideas have been worked on by scholars in the field.